Pengaruh Kualitas Sistem dan Kualitas Layanan Terhadap Kepuasan Pelanggan dan Niat Beli Ulang dengan Citra Merek sebagai Variabel Mediasi : Studi Pengiriman Makanan Secara Online di Kota Medan - Haneemsipatma, Agis; Jufrizen, Jufrizen (Jurnal Ilmu Manajemen, 2024)
This study aims to determine the effect of system quality and service quality on customer satisfaction and repurchase intentions with the brand image as a mediating variable: a study of online food delivery in Medan. . The method used in this research is the quantitative method with the population of all people in Medan City who actively use online food delivery applications (Shopee Food, GrabFood, and GoFood). The data collection technique used purposive sampling of 100 samples. The data analysis test technique used in this study is to use a variance-based structural equation model (SEM) with partial least square (PLS) by testing the outer model and inner model. This study succeeded in finding partial mediation of system quality through the brand image on service quality for users of online food delivery applications in Medan City, while the brand image variable was unable to mediate system quality on repurchase intentions. The results also show a positive and significant effect of system quality on service quality, customer satisfaction on repurchase intentions, brand image on service quality, and brand image on repurchase intentions on the use of online food delivery applications in Medan